Pelatihan Pembuatan Website Pembelajaran berbasis Google Sites bagi Guru Di SMP Negeri 23 Banjarmasin - Rizkiana, Fitria; Raden Roro Ariessanty Alicia Kusuma Wardhani; Okviyoandra Akhyar (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
This community service activity aimed to enhance teachers’ competence in developing digital learning media through a training program on creating learning websites using Google Sites at SMP Negeri 23 Banjarmasin. The training was motivated by the need for teachers to adapt to the rapid development of information and communication technology in the learning process. The program was conducted using a training and mentoring approach, which included stages of socialization, demonstration, hands-on website creation practice, and evaluation. The activity involved 27 teachers, and the evaluation was carried out using a closed-ended questionnaire covering two aspects: teachers’ enthusiasm and understanding of the training materials. The analysis revealed that, in terms of enthusiasm, 85.19% of participants were categorized as very high and 14.81% as high. In the aspect of understanding, 59.26% of participants were categorized as very high and 40.74% as high. These findings indicate that the training was highly effective in enhancing participants’ motivation and ability to develop learning websites. The program had a positive impact on improving teachers’ digital literacy and encouraging the integration of technology-based learning in schools. It is recommended that similar training programs be continued through follow-up mentoring and expanded to other schools to strengthen digital transformation in education.